Student dropout in the self-assessment projects of Graduate Programs in Education in Brazil (Práxis Educativa, 2025)
The 2019 Self-Assessment Report of Graduate Programs from the Coordination for the Improvement of Higher Education Personnel (CAPES) suggested that, in their self-assessment processes, programs should investigate the reasons for student dropout. Self-assessment of stricto sensu Graduate Programs was then incorporated into the CAPES evaluation form for the four-year evaluation cycle—2021-2024. Considering that student dropout has become a growing phenomenon in graduate education, this study focused on the field of Education—one of the areas with the largest number of programs in the country—with the aim of analyzing how student dropout is addressed in the self-assessment projects of Graduate Programs in Education between 2019 and 2024. To this end, the study adopts a mixed-methods approach, combining literature review and documentary research. The results indicate that, of the 23 programs selected, three have consolidated self-assessment projects, but none implemented the suggestion to include student dropout as a topic of discussion. It is also inferred that the absence of specific policies to address dropout in graduate education represents a limitation within the Brazilian educational policy agenda.Keywords: Student self-assessment. Student dropout. Graduate education policy.